O ingresso de jovens nos Colégios Tiradentes da Brigada Militar/RS : um sonho dos jovens ou só um meio para se atingir a um fim? - Martins, Isabel Cristina dos Santos (2017)
This dissertation aim to meet the students of the CTBM – Colégios Tiradentes da Brigada Militar (Tiradentes Colleges of the Military Brigade), in the State of Rio Grande do Sul, in the context that they are inserted, identifying socioeconomic and cultural features, tracing their school trajectory and pointing out the factors that influenced the choice of young people for the CTBM of their region, with the main theme: “The entrance of young students at Colégios Tiradentes da Brigada Militar: a dream of young people or just a way to get an ending?”. This was developed in two phases. In the first phase, quantitative, after completing the stages of evaluation and approval of the Project by the Scientific Commission of the School of Humanities and the Comitê de Ética em Pesquisa - CEP – (Research Ethics Committee) of the Pontifícia Universidade Católica do Rio Grande do Sul - PUCRS, in order to obtain an overview of the schools, an online questionnaire was applied, which was answered, voluntarily, by five hundred and ninety-six (596) students of the seven colleges. In the second qualitative phase, the data were obtained through semi-structure interviews conducted individually with twenty-one (21) students, randomly selected, with three (03) per school, representing each school year (1st., 2nd. and 3rd.). Seven (7) interviews were selected, one per school, for data’s analysis. The qualitative data were analyzed using the Análise Textual Discursiva - ATD (Discursive Textual Analysis) method, proposed by Moraes and Galiazzi (2013), and complemented with the quantitative data, which were tabulated with Google Docs’help. Based on the data that emerged from the field, in the studies formulated by several authors, among them: Estrela (1992), Maffesoli (1996, 1998), Falcão (2000), Krawczuyk (2011), Dayrell (2013), Dayrell, Carrano and Maia (2014), Abramovay (2012, 2015), Souza (2016), in the analysis of documents and field records, it was possible to verify that the young students of the CTBM reflect a youthful diversity, it is separated by the diversity that constitutes it (ABRAMOVAY, CASTRO, 2006). They are young people that accompany their parents’concern about the future and their formation in the present, but they desire selfrealization and respect for their decisions. Therefore, they are young, like so many other young people, who experience cultures and contexts, to constitute, as citizens, an integral human formation. Being in the CTBM and living with their rites is a dream of only a few students who expressed their affinity with the military career and wish they could continue their training in the Military Police Higher Course, if it were still possible. However, I also noticed that it became the dream of most of the young people who, when they first came to the schools, looking for means of accessing higher education, for the most varied courses, eventually realized how much learning could lead to their lives, considering the studies and the affective relationships that created and maintained in this space of formation. These young people give life to school, standing their history, rites and representations, while claiming changes in what they consider important for personal and group growthness. And, therefore, they demonstrate that they have a great potential for social contribution and political idealization for society and for the country they are in, aiming to help other young people to change their reality, so that they have access to the same opportunities that they had before.